Complex Age- and Cancer-Related Changes in Human Blood Transcriptome—Implications for Pan-Cancer Diagnostics - Qi, Fei; Gao, Fan; Cai, Ye; Han, Xueer; Qi, Yao; Ni, Jiawen; Sun, Jianfeng; Huang, Shengquan; Chen, Shaohua; Wu, Chunlin; Kapranov, Philipp (Frontiers in Genetics, 2021)
Early cancer detection is the key to positive clinical outcome. While a number of early diagnostics methods exist in clinics today, they tend to be invasive and limited to few cancer types. Thus, a clear need exists for non-invasive diagnostics methods that can be used to detect presence of cancer of any type. Liquid biopsy based on analysis of molecular components of peripheral blood has shown significant promise in such pan-cancer diagnostics, however, existing methods based on this approach require improvements, especially in sensitivity of early-stage cancer detection. The improvement would likely require diagnostics assays based on multiple different types of biomarkers and thus calls for identification of novel types of cancer-related biomarkers that can be used in liquid biopsy. Whole-blood transcriptome, especially its non-coding component, represents an obvious yet under-explored biomarker for pan-cancer detection. In this study, we show that whole transcriptome analysis using RNA-seq could indeed serve as a viable biomarker for pan-cancer detection. Furthermore, a class of long non-coding (lnc) RNAs, very long intergenic non-coding (vlinc) RNAs, demonstrated superior performance compared to protein-coding mRNAs. Finally, we show that age and presence of non-blood cancers change transcriptome in similar, yet not identical, directions and explore implications of this observation for pan-cancer diagnostics.